Answer:
d
Step-by-step explanation:
=-4
Answer:
The answer to your question is x ≠ -10 x ≠ 2 x ≠ -2
Solution
Step-by-step explanation:
Process
1.- Factor all the polynomials
= ![\frac{(x-8)(x + 5)}{(x + 10)(x- 2)} / \frac{(x+ 8)(x + 5)}{(x + 10)(x + 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-8%29%28x%20%2B%205%29%7D%7B%28x%20%2B%2010%29%28x-%202%29%7D%20%2F%20%5Cfrac%7B%28x%2B%208%29%28x%20%2B%205%29%7D%7B%28x%20%2B%2010%29%28x%20%2B%202%29%7D)
2.- Invert the second term
= ![\frac{(x- 8)(x + 5)}{(x +10)(x - 2)} \frac{(x+ 10)(x + 2)}{(x + 8)(x +5)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%208%29%28x%20%2B%205%29%7D%7B%28x%20%2B10%29%28x%20-%202%29%7D%20%20%5Cfrac%7B%28x%2B%2010%29%28x%20%2B%202%29%7D%7B%28x%20%2B%208%29%28x%20%2B5%29%7D)
3.- Simplify
= ![\frac{(x- 8)(x + 2)}{(x + 8)(x - 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%208%29%28x%20%2B%202%29%7D%7B%28x%20%2B%208%29%28x%20-%202%29%7D)
4.- x must be different to
x ≠ -10 x ≠ 2 x ≠ -2
This values are from the factor expressions and then equal to zero.
Step-by-step explanation:
f(x) = x² + 2x - 4
g(x) = 3x + 1
f(g(x)) = f(3x + 1)
f(3x + 1) = [3x + 1]² + 2[3x + 1] - 4
= 9x² + 6x + 1 + 6x + 2 - 4
= 9x² + 12x -1
Answer: ↓↓↓
Step-by-step explanation:
1. 13 < x < 21
2. 28 < x < 76
3. 24 < x < 42
4. 1 < x < 33
To find the number behind the x, just find the difference between the two numbers but make sure it's positive. Finding the number in front of the x, you add the two numbers together. X has to be greater than the smaller number but less than the greater number because to make a triangle, if two sides are added, their sum should be greater than the third side.
Hope that helped!